2004
DOI: 10.1111/j.1439-0434.2004.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus niger and Aspergillus carbonarius in Corinth Raisin and Wine‐Producing Vineyards in Greece: Population Composition, Ochratoxin A Production and Chemical Control

Abstract: Vineyard surveys of Corinth raisin cultivar carried out in the Peloponnese region of Greece during 2002 and of wine-producing grape cultivars (Cabernet Sauvignon and Grenache Rouge) on the island of Rhodes, Greece, during 2003, demonstrated the occurrence of various Aspergillus spp. in berries of bunches at harvest. Aspergillus niger and A. carbonarius were predominantly isolated from sampled berries. Although the prevailing Aspergillus spp. isolates belonged mainly to A. niger aggregate, isolates of A. carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 18 publications
5
63
0
2
Order By: Relevance
“…The latter mixture was confirmed as effective in a number of field trials carried out in several Mediterranean countries, including France, Spain, Greece and Italy (Tjamos et al 2004;Kappes et al 2005;Bellì et al 2007). The most effective treatment was observed at 21 days before harvesting and a previous treatment at veraison was suggested in high-risk conditions.…”
Section: Chemical and Biological Control Of Ota-producing Fungimentioning
confidence: 95%
“…The latter mixture was confirmed as effective in a number of field trials carried out in several Mediterranean countries, including France, Spain, Greece and Italy (Tjamos et al 2004;Kappes et al 2005;Bellì et al 2007). The most effective treatment was observed at 21 days before harvesting and a previous treatment at veraison was suggested in high-risk conditions.…”
Section: Chemical and Biological Control Of Ota-producing Fungimentioning
confidence: 95%
“…Previous studies demonstrated that mainly yeast species and members of the genera Aspergillus, Penicillum, Alternaria, Cladosporium, and Botrytis prevailed among fungi colonizing grapes (Battilani and Pietri, 2002;Tjamos et al, 2004;Serra et al, 2005). In addition, Nectria haematococca (synonyms: Fusarium solani, H. haematococca), A. niger and A. awamori, as well as P. expansum, P. chrysogenum, and P. crustosum were among the species isolated from grapes (Benkhemmar et al, 1993;Omer et al, 1995;Magnoli et al, 2004).…”
Section: Characterization Of Fungal Culturable Diversity: Microbial Amentioning
confidence: 99%
“…Therefore, care must be taken before the application of chemical products and field trials are imperative. Tjamos et al [118] evidenced the effectiveness of Switch (active ingredients cyprodinil and fludioxonil) in reducing the level of Aspergillus section Nigri populations on wine-producing grape vineyards and indicated that the closer the harvest the more efficient the application. Bellí et al [119] compared the effectiveness of Switch and Chorus (active ingredient cyprodinil) to control black Aspergilli in the vineyards.…”
Section: Control and Detoxification Methods To Reduce Ota Content In mentioning
confidence: 99%